Predictors of Mortality in Newborn Admitted in Special Care Baby Unit (SCABU) of Dhaka Shishu Hospital - Kamal, MA; Hoque, Mahbubul (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: The current neonatal mortality rate of Bangladesh is very high compared to developed countries. Objective: The objective of the study was to find out the predictors that are associated with mortality in newborn admitted in Special Care Baby Unit (SCABU) of Dhaka Shishu (Children) Hospital. Methods: This prospective study was conducted in the SCABU of Dhaka Shishu (Children) Hospital from 1st June 2016 to 30 November 2016. A semi-structured questionnaire was prepared before the study. Data were collected from the attendents of each neonate by asking questions who died at the neonatal period after hospital admission. Detail history regarding gestational age, birth weight, place of birth, person conducting delivery, mood of delivery, problem at birth, residence, reasons of referral, vehicle during transport, condition of baby at arrival, time taken during transport and need for any resuscitation was recorded. Data were analyzed by using SPSS version 16. Result: Total 970 neonates were admitted during data collection period out of them 98(10.10%) died. Majority (58.16%) of the death occurred in neonate who was admitted before 72 hours of age having gestational age <37 weeks (65.31%). Majority of the neonates were from urban area (56.12%) but from poor socioeconomic status (54.08%) and only 32.65% were on regular antenatal care. Majority were delivered by normal delivery at home and attended by TBA. Among the neonates 30.61% reached hospital only by ambulance and 64.29% were found hypothermic during admission. Majority 70(71.43%) were died within 24 hours of hospital admission. Neonatal sepsis, perinatal asphyxia and prematurity contributed majority of neonatal death. Conclusion: Early (age <72 hours) and premature neonates, neonates from poor socioeconomic background, lack of antenatal care, home delivery, lack of facility in local areas, inadequate transport and unstable initial condition contributed majority of neonatal death. Neonatal sepsis, perinatal asphyxia and prematurity contributed most of neonatal death. DS (Child) H J 2019; 35(2) : 123-129